Can generic knee joint models improve the measurement of osteoarthritic knee kinematics during squatting activity?. Issue 1 (2nd January 2017) - Clément, Julien; Dumas, Raphaël; Hagemeister, Nicola; de Guise, Jaques A.
Abstract: Knee joint kinematics derived from multi-body optimisation (MBO) still requires evaluation. The objective of this study was to corroborate model-derived kinematics of osteoarthritic knees obtained using four generic knee joint models used in musculoskeletal modelling – spherical, hinge, degree-of-freedom coupling curves and parallel mechanism – against reference knee kinematics measured by stereo-radiography. Root mean square errors ranged from 0.7° to 23.4° for knee rotations and from 0.6 to 9.0 mm for knee displacements. Model-derived knee kinematics computed from generic knee joint models was inaccurate. Future developments and experiments should improve the reliability of osteoarthritic knee models in MBO and musculoskeletal modelling.